GAMBARAN FOTO THORAX DAN DISTRIBUSI BAKTERI PATOGEN PADA PASIEN PNEUMONIA - Finaldi, Fauzan (Universitas Kristen Krida Wacana, 2024)
Pneumonia is an acute infectious or inflammatory disease that affects the lung parenchyma which can be caused by microorganisms such as bacteria, viruses and fungi. This study aims to determine the chest x-ray picture and the distribution of pathogenic bacteria in pneumonia patients, as well as to look at the chest x-ray picture of certain pathogens. The method in this study is to search for articles via Google Scholar and Pubmed. The results showed that the distribution of pathogenic bacteria in pneumonia cases varied, but the most common bacteria that cause pneumonia were Streptococcus pneumoniae, Klebsiella pneumoniae, and Mycoplasma pneumonia. On chest x-rays, the chest x-ray images obtained are quite diverse, and the commonly found results are consolidation, infiltrates and pleural effusion. In patients with pneumonia due to Mycoplasma pneumoniae, the chest x-ray picture that is often found is lobar pneumonia or lobar consolidation.